The Neutrophil to Lymphocyte Ratio and Other Full Blood Count Indices in Retinal Diseases: A Systematic Review of the Literature - Dimitrios Kazantzis; Genovefa Machairoudia; Panagiotis Theodossiadis; Irini Chatziralli (Medicina)
Background and Objectives: The neutrophil to lymphocyte ratio (NLR) and other full blood count indices have been used as a marker of inflammation in a variety of diseases. The aim of the current review is to summarize the existing knowledge on the use of these indices in retinal diseases. Materials and Methods: A systematic review of the literature was conducted to find eligible articles. The PUBMED and Scopus databases were systematically searched for relevant studies examining full blood count indices in retinal diseases. Results: The NLR was elevated in a number of vitreoretinal conditions, such as wet age-related macular degeneration (AMD), diabetic retinopathy and retinal vein occlusion, compared to controls. Full blood count indices could be useful in predicting the response to anti-VEG treatment in patients with wet AMD or diabetic macular edema (DME). Conclusions: The NLR and other indices can be used as diagnostic markers in retinal diseases and as prognostic factors of the response to treatment. The small sample size and short follow-up of the included studies and the variation in the measurement and cutoffs used for the NLR are limitations of its use in retinal conditions. Future studies need to further validate these findings and try to establish a link between these ratios and retinal phenotypes.